2015
DOI: 10.1093/brain/awv130
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional functional connectivity maps of neural oscillations in focal epilepsy

Abstract: Intractable focal epilepsy is a devastating disorder with profound effects on cognition and quality of life. Epilepsy surgery can lead to seizure freedom in patients with focal epilepsy; however, sometimes it fails due to an incomplete delineation of the epileptogenic zone. Brain networks in epilepsy can be studied with resting-state functional connectivity analysis, yet previous investigations using functional magnetic resonance imaging or electrocorticography have produced inconsistent results. Magnetoenceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
183
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(201 citation statements)
references
References 63 publications
12
183
3
Order By: Relevance
“…They found a positive predictive value for an Engel's class Ia outcome in 70 % of the patients who had high coherence in the area of the later resection. More recently [13] looked at the regional and global functional connectivity of MEG coherence in patients with Epilepsy, based on a 1 min resting state scan. This study used a beamforming technique to image the underlying sources.…”
mentioning
confidence: 99%
“…They found a positive predictive value for an Engel's class Ia outcome in 70 % of the patients who had high coherence in the area of the later resection. More recently [13] looked at the regional and global functional connectivity of MEG coherence in patients with Epilepsy, based on a 1 min resting state scan. This study used a beamforming technique to image the underlying sources.…”
mentioning
confidence: 99%
“…Keller et al (2015) demonstrated that patients with mesial temporal lobe epilepsy with persistent seizures who underwent amygdalohippocampectomy had significant atrophy of the bilateral dorsomedial and pulvinar thalamic regions. They also found that patients with persistent seizures had alterations of DTI-derived thalamotemporal probabilistic paths bilaterally, relative to those patients who were rendered seizure-free (Englot et al, 2015;Keller et al, 2015;Xu et al, 2014). Another study demonstrated that patients with unsuccessful surgical outcomes in mesial temporal lobe epilepsy demonstrated larger interhemispheric voxel-mirrored homotropic connectivity differences than those patients with successful surgical outcomes (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Another study demonstrated that patients with unsuccessful surgical outcomes in mesial temporal lobe epilepsy demonstrated larger interhemispheric voxel-mirrored homotropic connectivity differences than those patients with successful surgical outcomes (Xu et al, 2014). Moreover, a magnetoencephalography study revealed that patients with increased regional connectivity within the resection T A B L E 3 Results of multivariate analysis of variables that are predictive of a poor response to antiepileptic drugs site were more likely to achieve postoperative seizure freedom than those with neutral or decreased regional connectivity in focal epilepsy (Englot et al, 2015). These previous studies have suggested that brain connectivity can be a potential biomarker for predicting responses to epilepsy treatment.…”
Section: Discussionmentioning
confidence: 98%
“…This does not rule out a focal onset though, as in true focal epilepsies we can also encounter that the focal disease only reveals itself because of a general lowering of the seizure generating threshold. As much as focal epilepsy can be considered a general brain network disorder (Englot et al, 2015), generalized epilepsies encounter some focal characteristics. Instead of the black-and-white division we might want to put epilepsy syndromes more in a gradual distribution between focal and generalized.…”
Section: See Article Pages Xxx-xxxmentioning
confidence: 99%